2018
DOI: 10.1101/284968
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Metabolic modeling of Pectobacterium parmentieri SCC3193 provides insights into metabolic pathways of plant pathogenic bacteria

Abstract: 20 21Understanding the plant-microbe interactions are crucial for improving plant productivity and 22 plant protection. The latter aspect is particularly relevant for sustainable agriculture and 23 development of new preventive strategies against the spread of plant diseases. Constraint-based 24 metabolic modeling is providing one of the possible ways to investigate the adaptation to 25 different ecological niches and may give insights into the metabolic versatility of plant 26 20, 2018; pathogenic bacteria… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 47 publications
(59 reference statements)
0
3
0
Order By: Relevance
“…Soft rot bacteria present in soil niches are capable of colonizing healthy potato roots and invading the vascular systems, facilitating the spreading of this pathogen (Charkowski, 2018; Skelsey et al, 2018). In a recent study, metabolic modelling of P. parmentieri SCC3193 revealed that this phytopathogen can adapt to different ecological niches, such as soil and rhizosphere, through reconstitution of its metabolic pathways, allowing its survival on plant debris for large periods without interacting with its natural host (Zoledowska et al, 2019). Following these background studies, we evaluated the specificity of our multiplex qPCR using DNA isolated from soil and the rhizosphere of infected plants (Figure 6c).…”
Section: Discussionmentioning
confidence: 99%
“…Soft rot bacteria present in soil niches are capable of colonizing healthy potato roots and invading the vascular systems, facilitating the spreading of this pathogen (Charkowski, 2018; Skelsey et al, 2018). In a recent study, metabolic modelling of P. parmentieri SCC3193 revealed that this phytopathogen can adapt to different ecological niches, such as soil and rhizosphere, through reconstitution of its metabolic pathways, allowing its survival on plant debris for large periods without interacting with its natural host (Zoledowska et al, 2019). Following these background studies, we evaluated the specificity of our multiplex qPCR using DNA isolated from soil and the rhizosphere of infected plants (Figure 6c).…”
Section: Discussionmentioning
confidence: 99%
“…In a more recent study based on mass spectrometry analyses of immunoprecipitated effector–host target protein complexes in Nicotiana benthamiana , the deduced protein–protein interaction network revealed the cellular vesicle trafficking machinery as a major effector-targeted process ( Petre et al, 2021 ). In other studies, GEMs have been reconstructed for the bacterial plant pathogens Ralstonia solanacearum , Xanthomonas oryzae , and Pectobacterium parmentieri ( Peyraud et al, 2016 ; Zoledowska et al, 2018 ; Koduru et al, 2020 ), and for the fungus Sclerotinia sclerotiorum ( Peyraud et al, 2019 ). However, despite the abundance of omics data for many plant pathogens, very few have been analyzed from a systems biology perspective.…”
Section: Systems Biology Of Pathogens and Host–pathogen Interactionsmentioning
confidence: 99%
“…In one study a protein-protein interaction network of Arabidopsis thaliana and various pathogens of different kingdoms uncovered that effectors from different pathogens convergently target the same host proteins (Weßling et al, 2014). In other studies, GEMs have been reconstructed for the bacterial plant pathogens Ralstonia solanacearum, Xanthomonas oryzae, and Pectobacterium parmentieri (Koduru et al, 2020;Peyraud et al, 2016;Zoledowska et al, 2019), and for the fungus Sclerotinia sclerotiorum (Peyraud et al, 2019). However, despite the abundance of omics data for many pathogens, very few have been analyzed from a systems biology perspective.…”
Section: Systems Biology On Pathogensmentioning
confidence: 99%